Culture media used in the micropropagation of orchids hybrids - Luzia Yuriko Miyata; Fabíola Villa (Semina: Ciências Agrárias, 2014)
In orchid cultivation, tissue culture has been an important and effective tool for obtaining good quality seedlings on a large scale and within a short period of time. This study aims to evaluate culture media on the in vitro growth and development of orchid hybrids. Seedlings 1-1.5 cm long, deriving from in vitro germination of seeds, were inoculated in 250 mL flasks containing 50 mL of culture medium, with salts from the media where each of them were treated. Treatments consisted of applying culture media (MS; DSD1; Knudson; B5; and WPM), combined with 5 orchid hybrids (CW1, CW2, CW3, CI e BLC). The media were added 2 g L-1 of activated charcoal and solidified with 5 g L-1 of agar, and their pH was adjusted to 5.8 ± 0.1, before autoclaving at 121°C and at 1.1 atm for 20 minutes. After sterilization of media, seedlings were inoculated in a laminar flow chamber and then kept in a growth room at the temperature of 25 ± 1ºC, with photoperiod of 16 h and irradiance of 32 ?mol.m–2.s–1. The experimental design was completely randomized, in a factorial 5 x 5 scheme, containing 6 seedlings per repetition. After 120 days, we evaluated root number, shoot number, leaf and root length, and fresh root weight. In in vitro cultivation of orchids, the media standing out are MS and DSD1 and the hybrids CI, CW1, and BLC.